Quality and stability of canola and sunflower oils blended with palm olein during frying and microwave heating - Zahrau Bamalli Nouruddeen, 1985- author; Md. Abbas Ali; Ida Idayu Muhamad, supervisor; Fakulti Kejuruteraan Kimia (2013)
Thesis (Sarjana Kejuruteraan (Bioproses)) - Universiti Teknologi Malaysia, 2013